Poromas with large lumens histopathologically mimicking syringocystadenoma papilliferum: Report of three cases. (26th June 2018) - Arakawa, Hiroki; Tanese, Keiji; Miura, Keiko; Ebata, Satoshi; Yamada, Daisuke; Masui, Yuri; Tanaka, Masaru; Saida, Toshiaki; Ansai, Shin‐ichi
Abstract: We report on three patients exhibiting tumours with exophytic pedunculated structures with eroded surfaces. All cases showed the basic histopathological features of poroma accompanied by large, invaginated ductal structures lined by multiple layers of columnar or cuboidal cells. The columnar cells of invaginated ductal/cystic structures focally exhibited subtle features reminiscent of decapitation secretion along with dense infiltration of plasma cells in the surrounding stroma, mimicking syringocystadenoma papilliferum.